2018
DOI: 10.1167/18.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Visual search in barn owls: Task difficulty and saccadic behavior

Abstract: How do we find what we are looking for? A target can be in plain view, but it may be detected only after extensive search. During a search we make directed attentional deployments like saccades to segment the scene until we detect the target. Depending on difficulty, the search may be fast with few attentional deployments or slow with many, shorter deployments. Here we study visual search in barn owls by tracking their overt attentional deployments-that is, their head movements-with a camera. We conducted a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Since there is an enormous evolutionary distance between humans and archerfish, and given similar findings in other vertebrates such as barn owls (Harmening, Orlowski, Ben-Shahar, & Wagner, 2011;Orlowski et al, 2015;Orlowski, Ben-Shahar, & Wagner, 2018), rats (Botly & De Rosa, 2011), and pigeons (P. M. Blough, 1984), we speculate that these four features are processed equally efficiently in vertebrates in general.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Since there is an enormous evolutionary distance between humans and archerfish, and given similar findings in other vertebrates such as barn owls (Harmening, Orlowski, Ben-Shahar, & Wagner, 2011;Orlowski et al, 2015;Orlowski, Ben-Shahar, & Wagner, 2018), rats (Botly & De Rosa, 2011), and pigeons (P. M. Blough, 1984), we speculate that these four features are processed equally efficiently in vertebrates in general.…”
Section: Discussionsupporting
confidence: 60%
“…For example, studies on barn owls (Harmening et al, 2011;Orlowski et al, 2015) show that orientation and luminance contrast elicit the parallel search mode in these birds. More recently, a low-contrast feature task and two conjunction tasks involving both high-and low-contrast orientation have demonstrated serial search in this species (Orlowski et al, 2018). Studies on pigeons, on the other hand, have demonstrated that shapes (D.S.…”
Section: Parallel and Serial Visual Search Across Vertebratesmentioning
confidence: 99%
“…Other taxa have also been trained on visual search tasks, including recent work with barn owls [ 142 , 143 ] ( Tyto alba ), zebrafish [ 144 ] ( Danio rerio ), and bumblebees [ 145 ] ( Bombus terrestris ). The latter study conditioned bees to associate specific colours with rewards, which they could detect in arrays of distractor colours.…”
Section: Literature Review: Results and Discussionmentioning
confidence: 99%
“…In animal studies, the animal must be trained to understand what constitutes the target, so it can then search, find, and select it when presented experimentally. This training can last up to several months (e.g., Orlowski, Ben-Shahar, & Wagner, 2018) and should be done with caution, as concluded from human studies, (Buračas & Albright, 1999;Nothdurft, Pigarev, & Kastner, 2009). Furthermore, since new training is required for every new visual-search experiment, testing the same animal on multiple types of visual-search tasks demands multiple training periods, which a time-consuming procedure.…”
Section: Efficient Search Inefficient Searchmentioning
confidence: 99%
“…Notably, instead of increasing the number of distracting objects as in a classic visual-search experiments, the researchers increased the difficulty level of discriminating between the target and the background. Also, rather than testing how the target's and distractor's features affect visual search per se, the research was aimed to test how different strategies such as cuing and sequential priming, which are used to obtain initial focal attention, affect the visual-search behavior (Bond & Kamil, 1999;Goto, Bond, Burks, & Kamil, 2014) In the last decade, barn owls have become a major animal model in saliency and visual search research (Harmening, Orlowski, Ben-Shahar, & Wagner, 2011;Orlowski et al, 2015;Orlowski et al, 2018). Unlike most species, barn owls lack practically all eye movement, which in fact aids in the observation of their visual behavior through head tracking.…”
Section: Efficient Search Inefficient Searchmentioning
confidence: 99%